A FINDING LIST OF BLUE STARS IN THE SOUTH GALACTIC POLE - CHAVIRA, E (Observatorio Astrofísico de Tonantzintla, Pue, Pue, Mex, 1954)
We present a list of 419 new blue stars found in the direction of the South Galactic Pole. The field is of 105 square degrees between right ascension 20h 30m to 5h 30m and declination -21 to -34.
BOL OBS TONAN TACUB
Keywords: FINDING LIST, BLUE STARS, SOUTH, GALACTIC POLE; ASTRONOMIA Y ASTROFISICA; COSMOLOGIA Y COSMOGONIA; ESTRELLAS